Hubungan Kelengkapan Pengisian Lembar Informed Consent Pasien Bedah dengan Mutu Pelayanan Rawat Inap - Romaden Marbun; Nanta Sigit; Vincensia Dea (FORUM ILMIAH KESEHATAN, 2021)
Informed consent is a tool to determine the patient's own fate in medical action. The completeness of informed consent sheet can be used for various purposes. These purposes include as evidence in legal cases, research and education materials and can be used as a tool for analysis and evaluation of the quality of services provided by hospitals. This research aims to find out the relationship between the completeness of informed consent with the quality of inpatient services at Panti Nirmala Hospital Malang. The research design used in this study was analytical observational research with correlation studies. The sample size of this study was 52. Sampling was done using probability sampling technique which was simple random sampling. Data were analyzed using the Chi Square test. In this study, it was obtained that the quality of medical records (inpatient services) was not good to have incomplete informed consent as many as 6 people (11.5%) and the quality of medical records (inpatient services) was not good to have complete informed consent as many as 0 people (0.0%). Then it was also obtained that the quality of medical records (inpatient services) both had incomplete informed consent completeness as many as 16 people (30.8%) and the quality of medical records (inpatient services) both had complete informed consent completeness as many as 30 people (57.7%). Based on the results of statistical tests, p-value was 0.009 (